Test and treat approach for tuberculosis infection amongst household contacts of drug-susceptible pulmonary tuberculosis, Mumbai, India - Shah, Daksha; Bhide, Sampada; Deshmukh, Rajesh; Smith, Jonathan P.; Kaiplyawar, Satish; Puri, Varsha; Yeldandi, Vijay; Date, Anand; Nyendak, Melissa; Ho, Christine S.; Moonan, Patrick K. (Frontiers in Tuberculosis, 2024)
Background Mumbai is one of the most densely populated areas in the world and is a major contributor to the tuberculosis (TB) epidemic in India. A test and treat approach for TB infection (TBI) amongst household contacts (HHC) is part of the national policy for TB preventive treatment (TPT). However, in practice, the use of interferon-gamma release assay (IGRA) tests for infection are limited, and prevalence of TBI in Mumbai is not known. Methods We conducted a cross-sectional study among HHCs exposed to persons with microbiologically-confirmed, drug-susceptible pulmonary TB that were notified for antituberculosis treatment in Mumbai, India during September–December, 2021. Community-based field workers made home visits and offered IGRA (QuantiFERON-TB® Gold In-Tube Plus) tests to HHC aged 5 years and older. After ruling out active TB disease, HHC with IGRA-positive test results were referred for TPT. All HHC were monitored for at least 24 months for progression to active TB disease. Results Among 502 HHCs tested, 273 (54%) had IGRA-positive results. A total of 254 (93%) were classified as TBI and were eligible for TPT, of which 215 (85%) initiated TPT, and 194 (90%) completed TPT successfully. There was substantial variation in rates of TBI per household. In 32% of households, all HHC (100%) were IGRA positive and in 64% of households >50% of HHC were infected. In all, 22 HHCs (4%; 22/558) were diagnosed with TB disease; of these, five HHC were diagnosed during follow up, of which three were IGRA positive and had no evidence of disease at initial screening but chose not to initiate TPT. Conclusion A test and treat strategy for HHC resulted in the detection of a substantial proportion of TBI and secondary TB cases. Home-based IGRA testing led to high participation rates, clinical evaluations, TPT initiation, and early diagnoses of additional secondary cases. A community-focused, test and treat approach was feasible in this population and could be considered for broader implementation.